Isolation, Characterization and Growth Optimization of Glufosunate Ammonium Degrading Bacteria from Farmlands Soil in Mubi - Kabiru Yakubu; Salihu Ibrahim; Ahmad Umar Bello; Abba Babandi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The persistent application of glufosinate ammonium as a non-selective herbicide in agricultural practices raises significant environmental concerns due to its potential accumulation and eco-toxicity. This study focused on the isolation, characterization, degradation and optimization of glufosinate ammonium degrading bacteria from agricultural soil in Mubi, Adamawa State, Nigeria. Three isolates were screened from mineral salt medium containing glufosinate ammonium herbicides as carbon source which are isolate GA1, GA2 and GA3 but the isolate GA3 strain show highest degradation potential of glufosinate ammonium compare to GA1 and GA2 which was determined by UV-spectrophotometer and further by LC-MS which showed degradation by 75.9% the GA3 strain was characterized morphologically and biochemically as gram positive, and through 16SrRNA gene sequencing and phylogenetic analysis confirmed isolate GA3 (94.45% 16SrRNA homology to Bacillus ). Optimization of the degradation condition was performed using the one factor at a time (OFAT) approach, which revealed that the strain has growth optima at 35oC, pH 7.0, 10 mg/L glufosinate ammonium, with 5% inoculum size, and 48 hours’ incubation peak growth, the GA3 stain had growth stimulated best with glutamic acid 1g/L, (nitrogen source), and sucrose 1g/L (carbon source), exposure to heavy metal revealed Zn,Cu, and Fe stimulate growth whereas Pb and Hg caused significant inhibition. (p<0.0001, ANOVA). Response surface methodology (RSM) optimization enhanced degradation efficiency with GA3 strain degrading 75.9% glufosinate ammonium, the model shows great fit to the quadratic model (R2=0.9552) for GA3strain (F=23.66., P<0.0001). The results revealed that GA3 strain is capable of significant glufosinate ammonium degradation, with optimized conditions enhancing degradation efficiency. This study revealed great potential of indigenous soil microbes in bioremediation of herbicides-contaminated environments and provide a foundation for the development of eco-friendly strategies to mitigate glufosinate pollution in agricultural systems.